Evolving a New Efficient Mode of Fructose Utilization for Improved Bioproduction in Corynebacterium glutamicum - Krahn, Irene; Bonder, Daniel; Torregrosa-Barragán, Lucía; Stoppel, Dominik; Krause, Jens P.; Rosenfeldt, Natalie; Meiswinkel, Tobias M.; Seibold, Gerd M.; Wendisch, Volker F.; Lindner, Steffen N. (Frontiers in Bioengineering and Biotechnology, 2021)
Fructose utilization in Corynebacterium glutamicum starts with its uptake and concomitant phosphorylation via the phosphotransferase system (PTS) to yield intracellular fructose 1-phosphate, which enters glycolysis upon ATP dependent phosphorylation to fructose 1,6-bisphosphate by 1-phosphofructokinase. This is known to result in a significantly reduced oxidative pentose phosphate pathway (oxPPP) flux on fructose (~10 %) compared to glucose (~60 %). Consequently, the biosynthesis of NADPH demanding products, e.g. L-lysine, by C. glutamicum is largely decreased, when fructose is the only carbon source. Previous works reported that fructose is partially utilized via the glucose specific PTS presumably generating fructose 6-phosphate. This closer proximity to the entry point of the oxPPP might increase oxPPP flux and consequently NADPH availability. Here, we generated deletion strains either lacking in the fructose-specific PTS or 1-phosphofructokinase activity. We used these strains in short-term evolution experiments on fructose minimal medium and isolated mutant strains, which regained the ability of fast growth on fructose as a sole carbon source. In these fructose mutants, the deletion of the glucose specific PTS, as well as the 6-phosphofructokinase gene, abolished growth, unequivocally showing fructose phosphorylation via glucose specific PTS to fructose 6-phosphate. Gene sequencing revealed three independent amino acid substitutions in PtsG (M260V, M260T, P318S). These three PtsG variants mediated faster fructose uptake and utilization compared to native PtsG. In-depth analysis of the effects of fructose utilization via these PtsG variants revealed significantly increased biomass formation, reduced side-product accumulation, and increased L-lysine production by 50 %.